Evaluations of extended finishing in feedlot cattle and frameworks for economic assessments of controlled trials - Horton, Lucas M. (My University, 2024)
Outcomes research in animal agriculture provides stakeholders with meaningful insights into health, production, and economics, where decision-makers often rely on well-conducted research to make evidence-based choices. While health and production are top priorities, economic incentive is often the driving factor for producers to implement new interventions or management strategies. Randomized controlled trials (RCTs) provide strong evidence for causal inference, yet economic outcomes from feedlot cattle RCTs are frequently underreported, or lack consistent, well-described methodologies. In recent decades, U.S. feedlot cattle have been fed to heavier endpoints (EPs), which raises health, production, and economic considerations. The primary objectives of this dissertation were: to address knowledge gaps for a lesser, but common revenue source in the feedlot – culled animals; to evaluate performance and carcass characteristics of feedlot heifers when fed to alternative EPs; to assess the economic implications of extending days-on-feed (DOF) for heifers and steers, accounting for economic risk; and to provide guidance on economic analysis of RCT data. In an observational study of feedlot culls (2,992) from four Kansas feedlots, it was found that prices received for culls were most correlated with cull cow prices, and that cull cow prices may be used to estimate revenue for culls by using proportion of the cull cow price, contingent on culled animal weight. This provides a basis for estimating revenue from animals culled from feedlots, or removed from RCTs in future economic assessments. Three RCTs conducted at commercial feedlots in Kansas and Texas were pooled for a more robust assessment of heifer performance and carcass impacts when extending DOF. When feeding heifers to later EPs, live performance metrics such as daily weight gain and feed efficiency decreased as DOF increased. However, the amount of carcass weight gain as a proportion of live weight gain increased with longer feeding. The distributions of Quality and Yield Grades (QG and YG) also shifted towards higher grades with extended DOF, which has economic implications when marketing on a premium and discount-based grid. Economic assessments of extended feeding used a partial budget framework, incorporating differing methodologies to account for economic risk. From the pooled RCT data, a sensitivity analysis evaluated the economic implications of extending heifer DOF under various pricing and market scenarios by varying key economic factors. Overall, extending DOF showed minimal economic benefit for feedlot heifers, with net returns for later-fed EPs being poorest under low fed cattle prices, and high feed and yardage prices. When extending DOF, marketing heifers on a carcass basis was more favorable than live marketing. To evaluate the economic implications of feeding steers to later EPs, a stochastic simulation model was developed to characterize net return distributions and evaluate risk under recent economic conditions with contemporary cattle populations. Industry and RCT data from a commercial trial in Texas were utilized for parameterization. Compared to an industry-standard EP, median net return differences worsened with each later-fed EP, whether marketing live or on a grid. Although later EPs had the potential for higher net returns, they also carried increased risk of greater losses. The most impactful variable in the model was the difference in fed cattle price across EPs, which varied to reflect marketing on different weeks. Other influential variables included corn price, fed cattle price, mortality risk, and the QG grid when grid marketing. This dissertation concludes by discussing various economic analyses, identifying the partial budget as the most pragmatic option for evaluating alternative interventions or management strategies from RCTs in animal agriculture. Recommendations for future economic assessments include explicitly stating the type of analysis, detailing price sources, and clearly describing methodologies. This work provides valuable information and guidance to industry stakeholders on the application and conduct of economic assessments on RCTs, and the considerations and economic risk associated with feeding cattle to later EPs.
Keywords: Beef; Cattle; Days-on-feed; Economics; Endpoint management; Feedlot